2008
DOI: 10.1002/gps.2028
|View full text |Cite
|
Sign up to set email alerts
|

A predictive depression pattern in mild cognitive impairment

Abstract: The affective characteristics of depression at referral and the persistence of depression were better predictors of conversion to AD than the simple presence or absence of depression measured at referral time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 21 publications
0
32
4
Order By: Relevance
“…This again suggests that MCI and mood are related and hints at the potential for a temporal element to the relationship, as the presence of MCI at baseline had an influence on the presence of depression at follow-up. However, mood problems at baseline were not associated with a change from no cognitive impairment to MCI, which reflects previous research (Panza et al, 2008;Steenland et al, 2012), or from MCI to dementia over the two year period, which again fits with some previous literature (Devier et al, 2009;Houde et al, 2008;Vicini Chilovi et al, 2009), but contrasts with other research findings (Gabryelewicz et al, 2007).…”
Section: Are MCI and Mood Problems Related?contrasting
confidence: 56%
See 2 more Smart Citations
“…This again suggests that MCI and mood are related and hints at the potential for a temporal element to the relationship, as the presence of MCI at baseline had an influence on the presence of depression at follow-up. However, mood problems at baseline were not associated with a change from no cognitive impairment to MCI, which reflects previous research (Panza et al, 2008;Steenland et al, 2012), or from MCI to dementia over the two year period, which again fits with some previous literature (Devier et al, 2009;Houde et al, 2008;Vicini Chilovi et al, 2009), but contrasts with other research findings (Gabryelewicz et al, 2007).…”
Section: Are MCI and Mood Problems Related?contrasting
confidence: 56%
“…Only one study found that a higher score on measures of depression was significantly more frequent in individuals who progress from MCI to dementia (Gabryelewicz et al, 2007). One study found that whilst there was no difference in the baseline levels of depressive symptoms between individuals who progressed to dementia and those who did not, the persistence of depressive symptoms increased risk of progression (Houde et al, 2008). A further study followed participants for 2.1 years and found that baseline NPI scores for depression were higher in those who progressed from MCI to dementia than in those who continued to be classified as having MCI, although this did not remain significant after correction for multiple…”
Section: Progression From MCI To Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Houde and colleagues [33] reported that the simple presence or absence of depression at referral did not predict progression from MCI to AD in 60 patients with A-MCI who were observed annually for an average of 4.3 years. However, positive answers to specifi c GDS questions that referred to "melancholic" affect and the persistence of depression over 2 to 3 years signifi cantly predicted cognitive deterioration that eventually led to AD.…”
Section: Patients With Depressive Symptoms: Clinical Characteristmentioning
confidence: 98%
“…Depression has been identified as a risk factor for the development of Alzheimer's disease [1], as a factor in the conversion of MCI to AD [2], and as a disorder affecting a significant number of individuals with AD [3]. The underlying biological mechanisms linking depression and AD are unclear.…”
Section: Introductionmentioning
confidence: 99%